Lightweight Communication Overhead Authentication Scheme Using Smart Card - Ahmed Y. F. Al_Sahlani; Songfeng Lu (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
Authentication takes its place to grant authorized user a remote access to certain online resources. As well, prevent unauthorized user from accessing that resources. Unforyunatly most of authentication schemes consider only security factors without taking in consideration the communication resources required. Recently, Li et. al. proposed an enhanced smart card based remote user password authentication scheme. We analyzed their scheme and we pointed out that, their scheme required high communication overhead. Furthermore, their scheme suffer from forgery, user impersonation and server impersonation attacks. Through this paper to address aforesaid weaknesses, we propose a Lightweight communication overhead authentication scheme using smart card. The security and performance analysis shows that, our proposed scheme is lightweight communication and computation cost as well secure and can withstand wide spectrum of malicious attacks, like forgery, insider, replay and stolen smart card attack. Besides, our scheme encompasses desired security attributes. Therefore, it is suitable for practical use compared to other related scheme.